The structure and specificity of immunoglobulins - Jeffrey, P (1989)
﻿ An investigation into the structures of the antigen-binding fragments (Fab) of mouse monoclonal immunoglobulins by X-ray crystallography, is presented. The family of immunoglobulins studied, Gloops 1-5, possess the ability to bind to both the peptide antigen and the parent protein: Hen Egg-white Lysozyme. The Gloop1 and Gloop4 Fabs were generated by proteolytic cleavage of the antibody, and crystallisation trials yielded crystals of uncomplexed Fabs of both species. Attempts to grow Fab:antigen complex crystals proved unsuccessful. Partial purification of the heterogeneous Gloop4 Fab was found to be essential for the success of the crystallisations. Data were collected on crystal forms of Gloop1, Gloop2 and Gloop4 on an area detector. The structures of three Gloop2 crystal forms were solved by the molecular replacement technique, using models consisting of Fab domain pairs. Two of the crystal forms were refined by molecular dynamics methods at maximum resolutions of 3.3Å and 2.8Å, and the third by rigid body methods alone at 3.5Å resolution. Analysis of the Gloop2 structures between the crystal forms and with other Fabs indicated no atypical features in the domains. The elbow bend of the Gloop2 Fabs differed by up to 7°. The relative association of variable and constant domain pairs was also seen to vary between the Fabs. The changes in domain pairing caused significant differences in the relative disposition of the complementarity determining regions (CDRs), although there was no evidence for conformational change within individual CDRs. The Gloop2 combining site is dominated by a groove of approximate dimensions 12Åx9Åx7Å, containing many aromatic side-chains and a pair of glutamic acid residues in analogous positions to a those found in a FabrHen egg-white Lysozyme complex.